Some results on the first Appell matrix function F1(A, B, B′, C;z, w). Issue 2 (1st February 2020) - Abd-Elmageed, H.; Abdalla, M.; Abul-Ez, M.; Saad, Nasser
ABSTRACT: New relations for the first Appell hypergeometric matrix function F 1 ( A, B, B ′, C ; z, w ) are obtained including generating matrix functions, contiguous relations, recursion formulas, differentiations and series.